STUDI PEMBUATAN NATA DARI KULIT PISANG (NATA DE BANANA SKIN) - Budi Suarti; Taufik ,; Aswan Riadi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
This study aims to find ways of making nata with a comparison of sugar and a long fermentation on the quality of nata de banana skin. This study uses a complete Randomized Design (CRD) factorial. The results of statistical analysis on each parameter: The amount of sugar and a long fermentation differ very real effect on yield. The number of long fermentation guladan different effect not significant (p> 0.05) on pH. Number of different sugars affect highly significant (p <0.01) to the TSS. The amount of sugar and a long fermentation different effect highly significant (p <0.01) of thickness. Treatment interaction effect is not significant (p> 0.05) of thickness. The amount of sugar and a long fermentation influence erbeda highly significant (p <0.01) against violence. Treatment interaction effect is not significant (p> 0.05) to violence. The amount of sugar and a long fermentation influence not differ significantly (p> 0.05) for color. Treatment interaction effect is not significant (p> 0.05) on colorKeywords: nata de banana skin, sugar, fermentation, banana